UMP and HsMA Germany are offering dual degree programme in business engineering - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUALA LUMPUR, 9 February 2022 - The strategic collaboration between Universiti Malaysia Pahang (UMP) and Mannheim University of Applied Sciences (HsMA) will expand international academic collaboration in leading German engineering education (Fachhochschule) in the country.